Reproductive toxicity of Novaluron in Bombyx mori (Lepidoptera: Bombycidae) and its impact on egg production. (June 2021) - Santorum, Marilucia; Gastelbondo-Pastrana, Bertha Irina; Scudeler, Elton Luiz; Santorum, Márcia; Costa, Rose Meire; Carvalho dos Santos, Daniela
Abstract: Bombyx mori was used as a model to evaluate the reproductive toxicity of Novaluron in insects. Morphological analyses of the testes and ovaries of B. mori throughout their life cycle revealed important alterations in the germ and somatic cells involved in spermatogenesis and oogenesis. We observed in all testicular developmental phases that Novaluron affected not only the organization, distribution and development of the cysts containing male germ cells, but also the morphological features of cell death. Similar cellular characteristics were found in the treated B. mori ovaries, suggesting the occurrence of cell death in both organs, in addition to a significant reduction in oviposition of eggs by female moths. We demonstrated reproductive toxicity of Novaluron to the nontarget beneficial insect silkworm, thus providing a theoretical basis for revealing the reproductive toxicity of this insecticide to other nontarget beneficial insects. Graphical abstract: Image 1 Highlights: Novaluron provoked cytotoxic effects in the testes and ovaries of B. mori. Novaluron caused reprotoxicity in all stages of development of B. mori. Novaluron negatively impacted the process of spermatogenesis and oogenesis. Novaluron impaired the egg production and oviposition of females moths B. mori. Novaluron affected the reproduction of B. mori by reducing the amount of egg.